Change in land use and vegetation of el Veladero National Park during the period (2005 -2021), Acapulco- Mexico (Revista de Investigaciones Universidad del Quindío, 2022)
The conservation of national parks is fundamental for the sustainability of the territories and to safeguard the biotic and abiotic resources of the ecosystems, such as soil and vegetation. Objective: to describe the change in land use and vegetation of El Veladero National Park from 2005 to 2021, in the city of Acapulco (Mexico). Methodology: descriptive type with multitemporal technique, using the databases of the competent institutions on geographic information data; subsequent construction of thematic maps of land use and vegetation in the periods 2005 to 20021. Results: during the period 2021 the low subcaducifolia forest and the oak forest reached a decrease, at the level of the city of Acapulco the growth of pastures and soil anthropization was identified. A high incidence of secondary vegetation is evident, which indicates pioneerism because of disturbed soils. Conclusions: The growth of human settlements is a multifactorial problem for the conservation of El Veladero National Park. The urban growth of the city of Acapulco has changed the vocation of the conservation soils.
Keywords: El Veladero; land use; national park; protected natural area; vegetation cover